Influence of component technology on growth, yield and economics of safflower (Carthamus tinctorius L.): Influence of component technology on growth, yield and economics of safflower (Carthamus tinctorius L.) - S V KHADTARE,; K C OMBASE,; D R MURUMKAR,; S K SHINDE,; L N TAGAD,; V B AKASHE,; H N AIWALE, (Journal of Oilseeds Research, 2020)
A field experiment was conducted to quantify the contribution of component technologies to the yield of safflower for two consecutive years in post rainy season from 2017-18 to 2018-19 at Solapur (MS). The experiment composed of eight treatments with three replications in RBD. The treatment T8 (T7 + Cycocel application @ 1000 ppm at bud initiation) obtained significantly higher seed yield (725.3 kg ha-1) than rest of the treatments. The magnitude of yield increase over control was 4 to 80 per cent and 25 to 43 per cent over farmers’ practice. The treatment showed significant changes in plant height, number of capitula/plant and 100 seed weight than rest of the treatments. In terms of economics, treatment T4 was found numerically superior in net returns and B: C ratio.